THE ROLE OF INQUIRY APPROACH AND COGNITIVE STAGE ON STUDENT’S MATHEMATICAL CRITICAL THINKING ABILITY AND SELF REGULATED LEARNING - Nana Sukarna; Utari Sumarmo; Rudi Kurniawan (Journal Of Educational Experts (JEE), 2020)
The goal of this research is to analize the role of inquiry approach (IA) and cognitive stage (CS) on students’mathematical critical thinking ability (MCTA) and self regulated learning in mathematics (MSRL). The research adopted a pretest and postest design and involved 60 eleventh grade students of  16 – 18 years old, a MCTA  test,  the TOLT, and Longeot test, and a MSRL scale, and student’s opinion on IA lessons. The study revealed that percentage of student’ CS, were as follow 11.7% at concrete stage, 65.0% at transition stage, and 23.3% at formal stage.  In further analysis the study  found that IA and CS took a good role on obtaining student’s MCTA, but not for MSRL.  The formal operational stage students obtained higher grades on MCTA than the transitional and concrete operational stages, conversely the concrete operational stage students obtained higher grades on MSRL than the formal and transitional operational. Students taught by  saintific approach (SA) realized more  difficulties in solving MCTA tasks than students getting treatment with IA.  The study also found 1) MCTA students whose learning with IA is better than SA at medium grade level 2) no association between MCTA and CS, MCTA and MSRL, and CS and MSRL.  Beside that, students performed intense  activities during the IA lessons such as to discuss acitvely, to solve problems enthutiastically, and to present their work in front of the class voluntary.